A glaze for electrical porcelain repair and preparation method thereof

By adding modified sepiolite and other components to the electro-ceramic repair glaze, the problems of large shrinkage and pinhole defects in traditional glaze during firing are solved, and the glaze surface is flat, weather resistance and mechanical strength are improved, while reducing the firing temperature and energy consumption.

CN119285227BActive Publication Date: 2025-03-14HUNAN GAOQIANG ELECTRICAL CERAMIC & APPLIANCE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411833958.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Traditional electro-ceramic repair glaze has defects such as large shrinkage and easy pinhole formation during drying and firing, resulting in uneven glaze surface after repair, insufficient weather resistance and mechanical strength.

Method used

By adding modified sepiolite and using it in combination with nano-lanthanum zirconate, spodumene, calcined talc, etc., the ratio and firing process parameters of each component are reasonably controlled, the firing temperature is reduced, and the weather resistance and mechanical strength of the glaze are improved.

Benefits of technology

It realizes the reduction of firing temperature while ensuring glaze quality, saves energy and costs, and improves the weather resistance and mechanical strength of the glaze, reducing appearance problems during defect repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of electric porcelain glazes, and specifically relates to a glaze for electric porcelain repair and a preparation method thereof. The electric porcelain repair glaze comprises the following raw materials in parts by weight: 25-28 parts of potassium feldspar, 5-10 parts of modified sepiolite, 8-15 parts of spodumene, 8-10 parts of calcite, 3-5 parts of calcined talc, 10-13 parts of quartz, 1.5-3 parts of aluminum powder, 4-6 parts of zirconium silicate, 6-8 parts of longyan soil, 1-3 parts of nano lanthanum zirconate, and 0.5-1.6 parts of carboxymethyl cellulose; the modified sepiolite of the invention can reduce the drying and firing shrinkage of the glaze, reduce bending deformation, and is not easy to form defects such as pinholes. It is used in combination with nano lanthanum zirconate, spodumene, calcined talc and other components to reduce the firing temperature. When used for defect repair, the glaze surface is flat and has good weather resistance and mechanical strength. In addition, the electric porcelain repair glaze of the invention can reduce the firing temperature under the premise of ensuring the quality of the glaze surface, saving energy and cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric porcelain glazes, and in particular relates to a glaze for repairing electric porcelain and a preparation method thereof. Background Art

[0002] Insulators, as a functional ceramic material widely used in power systems, play an irreplaceable role in power transmission, distribution and the manufacture of high-voltage electrical equipment due to their excellent electrical properties, mechanical strength and chemical stability. However, in actual use, insulators often suffer from surface damage, cracks and even fractures due to long-term exposure to harsh environments, such as extreme climate, chemical corrosion and mechanical stress. These problems not only affect the aesthetics of insulators, but more importantly, they may reduce their electrical performance and threaten the safe and stable operation of power systems. In addition, the insulator production process is long and the process is extremely complicated. In particular, the products calcined at the temperature of the kiln furnace will produce various appearance defects, which greatly reduces the qualified rate of insulators. As a key material in insulator repair, the selection and application of glazes are even more important. The quality of glazes directly affects the performance and life of repaired insulators. Although traditional glazes can meet the repair needs to a certain extent, they often have defects such as large shrinkage and easy formation of pinholes during drying and firing, resulting in uneven glazes after repair, insufficient weather resistance and mechanical strength. In order to overcome these defects, it is urgent to prepare repair glazes with excellent weather resistance.

[0003] Sepiolite is a fibrous hydrous magnesium silicate, and its crystals are layered chain structures. As a multifunctional mineral material, Sepiolite has good adsorption, rheological and catalytic properties due to its special pore structure and huge specific surface area. It is widely used in environmental engineering, energy-saving green building materials, composite catalysts, biomedicine and other fields. However, the brittleness of Sepiolite makes it easy to break or fragment during processing and use, and it has poor stability and is not easy to dry. This property limits its application in certain fields.

[0004] Based on the above background technology, the present invention provides a glaze for electrical porcelain repair, which reduces the firing temperature while ensuring the quality of the glaze by adding modified sepiolite and using it in combination with other ingredients, thereby saving energy and cost. Summary of the invention

[0005] The first object of the present invention is to provide a glaze for repairing electric porcelain, which introduces new properties by adding modified sepiolite, such as UV resistance, so that it has better weather resistance and wear resistance, and can improve the overall performance of the glaze when used for defect repair. In addition, the modified sepiolite is used in combination with nano-lanthanum zirconate, spodumene, calcined talc and other components, and the ratio of each component and the firing process parameters are reasonably controlled, so that the firing temperature can be reduced while ensuring the quality of the glaze, saving energy and cost.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A glaze for repairing electric porcelain, comprising the following raw materials in parts by weight: 25-28 parts of potassium feldspar, 5-10 parts of modified sepiolite, 8-15 parts of spodumene, 8-10 parts of calcite, 3-5 parts of calcined talc, 10-13 parts of quartz, 1.5-3 parts of aluminum powder, 4-6 parts of zirconium silicate, 6-8 parts of longyan soil, 1-3 parts of nano lanthanum zirconate, and 0.5-1.6 parts of carboxymethyl cellulose;

[0008] The preparation process of the modified sepiolite is as follows:

[0009] (1) treating sepiolite with acid solution and then adding it into water, then adding surfactant and ferric chloride, stirring and reacting at room temperature, filtering, washing, drying and calcining to obtain pretreated sepiolite;

[0010] (2) adding sodium carbonate, sodium phosphate and lignin into water, stirring and mixing them uniformly to obtain solution A; adding the pretreated sepiolite of step (1) into water, and then adding aluminum chloride, stirring and mixing them uniformly to obtain solution B; adding solution A into solution B under stirring and heating conditions, reacting for a period of time, filtering, washing, drying and calcining to obtain the modified sepiolite.

[0011] Furthermore, in step (1), the mass ratio of sepiolite, surfactant and ferric chloride is 100:(1-5):(6-9).

[0012] Furthermore, the calcination temperature in step (1) is 300-400° C. and the calcination time is 1-2 h.

[0013] Furthermore, the acid solution in step (1) is a nitric acid solution or a sulfuric acid solution, and the surfactant is sodium dodecylbenzene sulfonate.

[0014] Furthermore, the mass ratio of sodium carbonate, sodium phosphate, lignin, aluminum chloride, and pretreated sepiolite in step (2) is (15-20):(5-10):(30-40):(2-7):(85-95).

[0015] Furthermore, the stirring and heating temperature in step (2) is 60-70° C.; and the reaction time is 2-4 h.

[0016] Furthermore, the calcination temperature in step (2) is 200-300° C. and the calcination time is 2-3 hours.

[0017] Furthermore, the particle size of the nano lanthanum zirconate is 20-30 nm.

[0018] The second object of the present invention is to provide a method for preparing a glaze for electrical porcelain repair, which has a simple preparation process, low energy consumption, and is suitable for industrial production.

[0019] A method for preparing the above-mentioned glaze for electrical porcelain repair comprises the following steps:

[0020] Potassium feldspar, modified sepiolite, spodumene, calcite, calcined talc, quartz, aluminum powder, zirconium silicate, longyan soil, nano lanthanum zirconate and carboxymethyl cellulose are weighed according to the above weight parts, and stirred and mixed evenly to obtain the product.

[0021] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0022] 1. The present invention provides a glaze for repairing electric porcelain, wherein the glaze improves its wear resistance by adding modified sepiolite, and the ultraviolet resistance of sepiolite also makes the glaze have better weather resistance, and when used for defect repair, the overall performance of the glaze can be improved. Moreover, the modified sepiolite is used in combination with nano-lanthanum zirconate, spodumene, calcined talc and other components, and by reasonably controlling the ratio of each component and the firing process parameters, the firing temperature can be reduced while ensuring the quality of the glaze, saving energy and cost.

[0023] 2. In the preparation process of the modified sepiolite of the present invention, by pre-treating the sepiolite with a surfactant and ferric chloride, the surface area of ​​the sepiolite is increased on the one hand, and iron ions can enter the interlayer of the sepiolite at the same time, and it is subjected to pillaring modification after calcination to improve the stability of the sepiolite. Then the sol-gel method is adopted to form the composite of sepiolite aluminum oxide, and the carbonization of lignin adsorbed on the surface of the sepiolite during the calcination process further improves the stability and strength of the sepiolite. The modified sepiolite can reduce the drying and firing shrinkage of the glaze, reduce bending deformation, and is not easy to form defects such as pinholes. It is used in conjunction with components such as nano-lanthanum zirconate, spodumene, calcined talc, and reduces the firing temperature. When used for defect repair, the glaze surface is smooth and has good weather resistance and mechanical strength.

[0024] 3. The present invention provides a method for preparing a glaze for electrical porcelain repair, which has a simple preparation process, low energy consumption, and is suitable for industrial production. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0026] (1) Example

[0027] Example 1

[0028] A glaze for repairing electric porcelain, comprising the following raw materials in parts by weight: 26 parts of potassium feldspar, 7 parts of modified sepiolite, 12 parts of spodumene, 9 parts of calcite, 4 parts of calcined talc, 12 parts of quartz, 2 parts of aluminum powder, 5 parts of zirconium silicate, 7 parts of longyan soil, 2 parts of nano lanthanum zirconate, and 1.2 parts of carboxymethyl cellulose;

[0029] The preparation process of the modified sepiolite is as follows:

[0030] (1) 100 g of sepiolite was soaked in a 3% sulfuric acid solution for 5 h, filtered, washed, and dried, and then added into 1 L of water, and then 3 g of sodium dodecylbenzene sulfonate and 7 g of ferric chloride were added, and stirred at room temperature for 1.5 h. After the reaction was completed, the reaction liquid was filtered, the solid was collected, washed, and dried, and then calcined at 350 ° C for 1.5 h to obtain pretreated sepiolite;

[0031] (2) Add 17.5 g of sodium carbonate, 7.5 g of sodium phosphate and 35 g of lignin to 1 L of water, stir and mix to obtain solution A; add 90 g of the pretreated sepiolite prepared in step (1) to water, and then add 5 g of aluminum chloride, stir and mix to obtain solution B; add solution A to solution B under stirring and heating conditions at 65°C, react for 3 h, filter, wash, dry and calcine at 250°C for 2.5 h to obtain modified sepiolite.

[0032] A method for preparing a glaze for electrical porcelain repair comprises the following steps:

[0033] Potassium feldspar, modified sepiolite, spodumene, calcite, calcined talc, quartz, aluminum powder, zirconium silicate, longyan soil, nano lanthanum zirconate and carboxymethyl cellulose are weighed according to the above weight parts, and stirred and mixed evenly to obtain the product.

[0034] Example 2

[0035] A glaze for repairing electric porcelain, comprising the following raw materials in parts by weight: 25 parts of potassium feldspar, 5 parts of modified sepiolite, 8 parts of spodumene, 8 parts of calcite, 3 parts of calcined talc, 10 parts of quartz, 1.5 parts of aluminum powder, 4 parts of zirconium silicate, 6 parts of longyan soil, 1 part of nano lanthanum zirconate, and 0.5 parts of carboxymethyl cellulose;

[0036] The preparation process of the modified sepiolite is as follows:

[0037] (1) 100 g of sepiolite was soaked in a 3% sulfuric acid solution for 6 h, filtered, washed, and dried, and then added into 1 L of water, and then 1 g of sodium dodecylbenzene sulfonate and 6 g of ferric chloride were added, and stirred at room temperature for 1 h. After the reaction was completed, the reaction liquid was filtered, the solid was collected, washed, and dried, and then calcined at 400 ° C for 1 h to obtain the pretreated sepiolite;

[0038] (2) Add 15 g of sodium carbonate, 5 g of sodium phosphate, and 30 g of lignin to 1 L of water, stir and mix evenly to obtain solution A, add 85 g of the pretreated sepiolite prepared in step (1) to water, then add 2 g of aluminum chloride, stir and mix evenly to obtain solution B, add solution A to solution B under stirring and heating conditions at 60° C., react for 4 h, filter, wash, dry, and calcine at 300° C. for 2 h to obtain modified sepiolite.

[0039] A method for preparing a glaze for electrical porcelain repair comprises the following steps:

[0040] Potassium feldspar, modified sepiolite, spodumene, calcite, calcined talc, quartz, aluminum powder, zirconium silicate, longyan soil, nano lanthanum zirconate and carboxymethyl cellulose are weighed according to the above weight parts, and stirred and mixed evenly to obtain the product.

[0041] Example 3

[0042] A glaze for repairing electric porcelain, comprising the following raw materials in parts by weight: 28 parts of potassium feldspar, 10 parts of modified sepiolite, 15 parts of spodumene, 10 parts of calcite, 5 parts of calcined talc, 13 parts of quartz, 3 parts of aluminum powder, 6 parts of zirconium silicate, 8 parts of longyan soil, 3 parts of nano lanthanum zirconate, and 1.6 parts of carboxymethyl cellulose;

[0043] The preparation process of the modified sepiolite is as follows:

[0044] (1) 100 g of sepiolite was soaked in a 3% sulfuric acid solution for 7 h, filtered, washed, dried, and then added into 1 L of water, and then 5 g of sodium dodecylbenzene sulfonate and 9 g of ferric chloride were added, and stirred at room temperature for 2 h. After the reaction was completed, the reaction liquid was filtered, the solid was collected, washed, dried, and then calcined at 300 ° C for 2 h to obtain the pretreated sepiolite;

[0045] (2) Add 20 g of sodium carbonate, 10 g of sodium phosphate, and 40 g of lignin to 1 L of water, stir and mix evenly to obtain solution A, add 95 g of the pretreated sepiolite prepared in step (1) to water, then add 7 g of aluminum chloride, stir and mix evenly to obtain solution B, add solution A to solution B under stirring and heating conditions at 70° C., react for 2 h, filter, wash, dry, and calcine at 200° C. for 3 h to obtain modified sepiolite.

[0046] A method for preparing a glaze for electrical porcelain repair comprises the following steps:

[0047] Potassium feldspar, modified sepiolite, spodumene, calcite, calcined talc, quartz, aluminum powder, zirconium silicate, longyan soil, nano lanthanum zirconate and carboxymethyl cellulose are weighed according to the above weight parts, and stirred and mixed evenly to obtain the product.

[0048] (2) Comparative example

[0049] Comparative Example 1

[0050] The difference between Comparative Example 1 and Example 1 is that the modified sepiolite is replaced by sepiolite, and the rest is the same as Example 1.

[0051] Comparative Example 2

[0052] The difference between Comparative Example 2 and Example 1 is that the modified sepiolite is replaced by the pretreated sepiolite in step (1); the rest is the same as Example 1.

[0053] Comparative Example 3

[0054] The difference between Comparative Example 3 and Example 1 is that the nano-lanthanum zirconate is omitted; the rest is the same as Example 1.

[0055] (3) Test example

[0056] In order to illustrate the repair effect of the glaze obtained in Examples 1-3 and Comparative Examples 1-3, 60 electrical porcelains with appearance defects were selected and randomly divided into 6 groups, namely, Example 1-3 Group and Comparative Example 1-3 Group. Then, the glaze obtained in Examples 1-3 and Comparative Examples 1-3 and water were stirred and mixed evenly, and the mass ratio of glaze, water and ball was 1:0.5:1.5. After ball milling for 5 hours, the glaze was passed through a 200-mesh sieve to obtain a glaze slurry, and then the glaze slurry was applied to the parts of each group of electrical porcelains with appearance defects, and then subjected to a low-temperature melting treatment of 800°C and kept warm for 2 hours. Then, the following tests were performed on each group to show the repair effect.

[0057] Test Example 1

[0058] The appearance of the glazes treated with the glazes obtained in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the test standards of GB / T 772 and GB / T 1001.1. The test results are shown in Table 1.

[0059] Table 1

[0060]

[0061] It can be seen from the test results in Table 1 that the surface of the electric porcelain repaired with the glaze obtained in Examples 1-3 is smooth and flat, the glaze is bright and delicate, and there is no glaze, no glaze shrinkage, no pinholes and the like. It shows that the glaze for repairing electric porcelain prepared by the present invention will not produce appearance defects such as glaze shrinkage when melted at low temperature, and can be fully dissolved and leveled, and attached to the defective parts of the electric porcelain. However, since the preparation process of the modified sepiolite is changed in Comparative Examples 1 and 2, the smoothness and flatness of the repaired electric porcelain glaze is poor, there are ups and downs or ripples, and there are appearance defects such as glaze, glaze shrinkage, pinholes and the like to varying degrees. This result is because the modified sepiolite prepared in Examples 1-3 of the present invention has good dispersibility and fluidity, can be evenly distributed in the glaze, and helps to reduce defects such as bubbles and pinholes generated in the glaze during the firing process. Through the modification treatment, the microstructure and surface properties of the sepiolite are changed, so that its shrinkage behavior in the glaze is controlled, and the flatness and quality of the glaze are improved. At the same time, the introduction of ingredients such as spodumene and calcined talc also helps to improve the gloss and color stability of the glaze.

[0062] Test Example 2

[0063] (1) Testing the fluidity of the glaze slurries prepared in Examples 1-3 and Comparative Examples 1-3;

[0064] (2) Testing the porosity of the electrical porcelain coated with the glazes obtained in Examples 1-3 and Comparative Examples 1-3;

[0065] (3) Wear resistance: The wear resistance of the electric porcelain surface after coating with the glazes obtained in Examples 1-3 and Comparative Examples 1-3 was tested using a rotating rubber grinding wheel method according to the test standard of GB / T1768-2006;

[0066] (4) Bending strength and fracture toughness: According to the test standard of GB / T6569-2006, the bending strength and fracture toughness of the electric porcelain coated with the glazes obtained in Examples 1-3 and Comparative Examples 1-3 were tested;

[0067] (5) Weather resistance: At a test temperature of 30°C, select ultraviolet rays in the 365nm-420nm band with an average irradiation intensity of 300W / m 2 The electric porcelain glaze repaired with the glazes obtained in Examples 1-3 and Comparative Examples 1-3 was irradiated. After continuous irradiation for 1 month, the appearance changes such as the color and cracking of the glaze were observed, and whether the glaze surface showed fading, cracking, etc. was recorded.

[0068] The above test results are shown in Table 2.

[0069] Table 2

[0070]

[0071] As shown in the test results of Table 2, after the glaze obtained by using the embodiments 1-3 of the present invention is used to coat the surface of the electric porcelain, the electric porcelain has excellent bending strength and fracture toughness, and the wear amount and porosity are low, and the fluidity of the glaze slurry is 0.29. In addition, after 1 month of ultraviolet irradiation, the surface of the electric porcelain still has a good appearance quality. The present invention uses pre-treated sepiolite as a raw material, adopts a sol-gel method to form a composite of sepiolite aluminum oxide, and carbonizes the lignin adsorbed on the surface of the sepiolite during the calcination process, thereby further improving the stability and strength of the sepiolite. Therefore, adding the modified sepiolite with excellent stability and strength to the glaze can reduce the drying and firing shrinkage of the glaze, reduce bending deformation, and is not easy to form defects such as pinholes. After being used in combination with components such as nano lanthanum zirconate, spodumene, and calcined talc, the firing temperature can be reduced, and the glaze surface is smooth when used for defect repair, and has good weather resistance and mechanical strength.

[0072] Comparative Example 1 uses ordinary sepiolite, and its performance is the worst. Comparative Example 2 uses sepiolite pretreated with surfactant and ferric chloride, and its performance is improved compared with Comparative Example 1, but still not as good as Examples 1-3. This is because by pretreating sepiolite with surfactant and ferric chloride, on the one hand, the surface area of ​​sepiolite can be increased, and at the same time, iron ions can enter the interlayer of sepiolite, and after calcination, it is pillared and modified, which plays a role in improving the stability of sepiolite and improving the mechanical strength of glaze. It can be seen that the fiber morphology and microstructure of modified sepiolite also help to improve the mechanical strength of glaze, so that it can resist external shock and vibration during use, and reduce performance degradation or appearance changes caused by physical damage.

[0073] In the comparative example 3, no nano-lanthanum zirconate was added to the glaze, and the performance was also lower than that of Examples 1-3, which shows that the combination of nano-lanthanum zirconate and other ingredients such as modified sepiolite can further repair glaze defects and make the electrical porcelain have good weather resistance and mechanical strength.

[0074] The traditional production process of electric porcelain is long and the process is extremely complicated. In particular, the products calcined at the temperature of the kiln will produce various appearance defects. The normal qualified rate is generally only about 80%, of which nearly 15% of the unqualified products are caused by appearance defects. The present invention is aimed at electric porcelain with appearance defects. By designing a specific formula, the various components and their contents cooperate with each other and work together to improve the glaze's repair performance on defects. When using the repair glaze of the present invention for glazing, there is no need to fire at a high temperature of more than 1200°C, and it only needs to be fired at a temperature of 800°C. Therefore, by using the electric porcelain repair glaze described in the present invention, not only can the energy consumption rate be greatly reduced, but also waste products (unqualified) can be turned into genuine products, thereby increasing profits.

[0075] In summary, in the present invention, modified sepiolite is used in combination with nano-lanthanum zirconate, spodumene, calcined talc and other ingredients. By reasonably controlling the ratio of these ingredients and the firing process parameters, the firing temperature can be reduced while ensuring the glaze quality, thereby saving energy and cost.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A glaze for electrical porcelain repair, characterized in that: The invention comprises the following raw materials in parts by weight: 25-28 parts of potassium feldspar, 5-10 parts of modified sepiolite, 8-15 parts of spodumene, 8-10 parts of calcite, 3-5 parts of calcined talc, 10-13 parts of quartz, 1.5-3 parts of aluminum powder, 4-6 parts of zirconium silicate, 6-8 parts of longyan soil, 1-3 parts of nano lanthanum zirconate, and 0.5-1.6 parts of carboxymethyl cellulose; The preparation process of the modified sepiolite is as follows: (1) treating sepiolite with acid solution and then adding it into water, then adding surfactant and ferric chloride, stirring and reacting at room temperature, filtering, washing, drying and calcining to obtain pretreated sepiolite; (2) adding sodium carbonate, sodium phosphate and lignin into water, stirring and mixing them uniformly to obtain solution A; adding the pretreated sepiolite of step (1) into water, and then adding aluminum chloride, stirring and mixing them uniformly to obtain solution B; adding solution A into solution B under stirring and heating conditions, reacting for a period of time, filtering, washing, drying and calcining to obtain the modified sepiolite; in step (1), the mass ratio of the sepiolite, surfactant and ferric chloride is 100:(1-5):(6-9); the calcination temperature is 300-400°C and the time is 1-2h; in step (2), the mass ratio of sodium carbonate, sodium phosphate, lignin, aluminum chloride and pretreated sepiolite is (15-20):(5-10):(30-40):(2-7):(85-95); the calcination temperature is 200-300°C and the time is 2-3h.

2. The glaze for electrical porcelain repair according to claim 1, characterized in that: In step (1), the acid solution is a nitric acid solution or a sulfuric acid solution, and the surfactant is sodium dodecylbenzene sulfonate.

3. The glaze for electrical porcelain repair according to claim 1, characterized in that: The stirring and heating temperature in step (2) is 60-70° C.; and the reaction time is 2-4 hours.

4. The glaze for repairing electrical porcelain according to claim 1, characterized in that: The particle size of the nano lanthanum zirconate is 20-30 nm.

5. A method for preparing the glaze for electrical porcelain repair as claimed in claim 1, characterized in that: The following steps are involved: According to claim 1, potassium feldspar, modified sepiolite, spodumene, calcite, calcined talc, quartz, aluminum powder, zirconium silicate, Longyan soil, nano lanthanum zirconate, and carboxymethyl cellulose are weighed in parts by weight, and stirred and mixed evenly to obtain the product.

Citation Information

Patent Citations

  • Rare earth daily ceramic glaze and method using rare earth daily ceramic glaze to prepare daily ceramic

    CN108083646A

  • Antibacterial lasting ceramic glaze, ceramic with glaze and preparation method of ceramic

    CN118754437A